Efficient and Spatially Controlled Functionalization of SBA‐15 and Initial Results in Asymmetric Rh‐Catalyzed 1, 2‐Additions under Confinement. Issue 10 (9th April 2021) - Beurer, Ann‐Katrin; Kirchhof, Manuel; Bruckner, Johanna R.; Frey, Wolfgang; Baro, Angelika; Dyballa, Michael; Giesselmann, Frank; Laschat, Sabine; Traa, Yvonne
Abstract: Selectively functionalized mesoporous silica may considerably advance heterogeneous catalysis through the controlled immobilization of highly selective complex catalysts inside the mesopores. However, spatially controlled functionalization and the precise analytical verification are still a challenge. In this publication, we report a method, which ensures a selective functionalization of the mesopore surface with a clickable linker and thus makes it possible to study confinement effects during catalyzed reactions. First, we passivate the silanol groups on the particle surface and in the pore entrances of the mesoporous silica material SBA‐15 with 1, 1, 1‐trimethyl‐ N ‐(trimethylsilyl)silanamine. Then we remove the template by solvent extraction and functionalize the pore walls with 3‐azidopropyltriethoxysilane before we click the catalyst. In initial experiments of asymmetric Rh‐catalyzed 1, 2‐addition, we investigate the performance of a catalyst clicked selectively in the mesopores and compare it to the dissolved catalyst as well as to the catalyst immobilized exclusively on the external surface of SBA‐15. Abstract : Confined catalysis : For establishing a new method for the spatially controlled functionalization, azide groups are introduced exclusively into the mesopores of SBA‐15. Thus, a Rh complex active for asymmetric 1, 2‐addition could be immobilized unambiguously in the mesopores of SBA‐15 by click chemistry.